2013
DOI: 10.1080/1359432x.2013.865118
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the association of a high quality job and self-esteem over time: A multiwave study

Abstract: High self-esteem often predicts job-related outcomes, such as high job satisfaction or high status. Theoretically, high quality jobs (HQJs) should be important for self-esteem, as they enable people to use a variety of skills and attribute accomplishments to themselves, but research findings are mixed. We expected reciprocal relationships between self-esteem and HQJ. However, as work often is more important for the status of men, we expected HQJ to have a stronger influence on self-esteem for men as compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 88 publications
3
17
0
Order By: Relevance
“…This questionnaire is based on the job diagnostic survey (Hackman & Oldham, 1975), an instrument to assess social support (Frese & Zapf, 1987) and an instrument for stress-related work analyses (Semmer, 1984). These sub-scales are relevant for learning at work (Kammermann, Stalder, & Hättich, 2011;Keller, Meier, Gross, & Semmer, 2015;Nägele, 2013;Stalder & Carigiet Reinhard, 2014).…”
Section: Workplace Factorsmentioning
confidence: 99%
“…This questionnaire is based on the job diagnostic survey (Hackman & Oldham, 1975), an instrument to assess social support (Frese & Zapf, 1987) and an instrument for stress-related work analyses (Semmer, 1984). These sub-scales are relevant for learning at work (Kammermann, Stalder, & Hättich, 2011;Keller, Meier, Gross, & Semmer, 2015;Nägele, 2013;Stalder & Carigiet Reinhard, 2014).…”
Section: Workplace Factorsmentioning
confidence: 99%
“…Keller et al (2015) found self-esteem to be positively correlated with obtaining highquality jobs, but this relationship was only true for women. Keller et al (2015) interpreted their results as being linked to gender stereotypes in society, where it was more important for women than men to be 'liked' by others. Thus, according to the gendered beliefs in society, men are stereotypically seen as competitive and dominant, while women are seen as nurturing and socially competent (Keller et al 2015;Wood and Eagly 2012).…”
Section: Gender Differences In Self-esteemmentioning
confidence: 87%
“…Women/girls also tend to be judged based on their physical appearance to a higher degree than men/boys (Jones and Crawford 2006). Keller et al (2015) found self-esteem to be positively correlated with obtaining highquality jobs, but this relationship was only true for women. Keller et al (2015) interpreted their results as being linked to gender stereotypes in society, where it was more important for women than men to be 'liked' by others.…”
Section: Gender Differences In Self-esteemmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with high self-esteem and positive self-evaluations tend to have higher aspirations [28] and are more likely to apply for high-paying jobs [26] as well as more challenging jobs [28]. Finally, Keller et al [30] report that self-esteem is important for obtaining high quality jobs but only for women, suggesting that self-esteem is particularly pertinent to women's labor market opportunities. In sum, studies show that personality traits can explain part of the gender wage gap, but also that the valuation of certain traits can vary with both occupation and gender.…”
Section: Previous Research and Our Contributionmentioning
confidence: 99%